2009
DOI: 10.5194/bg-6-1127-2009
|View full text |Cite
|
Sign up to set email alerts
|

Wetland restoration and methanogenesis: the activity of microbial populations and competition for substrates at different temperatures

Abstract: Abstract. Ljubljana marsh in Slovenia is a 16 000 ha area of partly drained fen, intended to be flooded to restore its ecological functions. The resultant water-logging may create anoxic conditions, eventually stimulating production and emission of methane, the most important greenhouse gas next to carbon dioxide. We examined the upper layer (∼30 cm) of Ljubljana marsh soil for microbial processes that would predominate in water-saturated conditions, focusing on the potential for iron reduction, carbon mineral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 54 publications
9
42
0
Order By: Relevance
“…Longer-term flooding therefore increased, rather than reduced, the annual emissions by approximately 40 % and suggests that any increase in freshwater flooding in response to climate change could result in a significant increase in carbon dioxide emissions from these systems. The annual emissions of CO 2 found in this study are in line with those previously reported for floodplain wetlands (10.91 ± 0.54 Mg CO 2 -C ha −1 yr −1 ) (Batson et al, 2015), coastal plain wetlands (11.29 Mg CO 2 -C ha −1 yr −1 ) (Morse et al, 2012) and occasionally (9.7 Mg CO 2 -C ha −1 yr −1 ) or frequently flooded (13 Mg CO 2 -C ha −1 yr −1 ) riparian forests (Jacinthe, 2015). Our results are also in part agreement with other investigations on comparable ecosystems that examined the impact of flooding on GHGs (Morse et al, 2012;Jacinthe, 2015;Kim et al, 2015;Marín-Muñiz et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Longer-term flooding therefore increased, rather than reduced, the annual emissions by approximately 40 % and suggests that any increase in freshwater flooding in response to climate change could result in a significant increase in carbon dioxide emissions from these systems. The annual emissions of CO 2 found in this study are in line with those previously reported for floodplain wetlands (10.91 ± 0.54 Mg CO 2 -C ha −1 yr −1 ) (Batson et al, 2015), coastal plain wetlands (11.29 Mg CO 2 -C ha −1 yr −1 ) (Morse et al, 2012) and occasionally (9.7 Mg CO 2 -C ha −1 yr −1 ) or frequently flooded (13 Mg CO 2 -C ha −1 yr −1 ) riparian forests (Jacinthe, 2015). Our results are also in part agreement with other investigations on comparable ecosystems that examined the impact of flooding on GHGs (Morse et al, 2012;Jacinthe, 2015;Kim et al, 2015;Marín-Muñiz et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The annual emissions of CO 2 found in this study are in line with those previously reported for floodplain wetlands (10.91 ± 0.54 Mg CO 2 -C ha −1 yr −1 ) (Batson et al, 2015), coastal plain wetlands (11.29 Mg CO 2 -C ha −1 yr −1 ) (Morse et al, 2012) and occasionally (9.7 Mg CO 2 -C ha −1 yr −1 ) or frequently flooded (13 Mg CO 2 -C ha −1 yr −1 ) riparian forests (Jacinthe, 2015). Our results are also in part agreement with other investigations on comparable ecosystems that examined the impact of flooding on GHGs (Morse et al, 2012;Jacinthe, 2015;Kim et al, 2015;Marín-Muñiz et al, 2015). Jacinthe (2015) reported that CO 2 fluxes during summer were larger from a riparian forest affected by floods in winter and spring than from a flood protected area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Flooded, anoxic conditions also promote the growth and activity of methanogens, and lower diffusion rates can also trap more CH 4 in the soil. However, the increased availability of Fe(III) could competitively inhibit methane production (Roden and Wetzel, 1996;Bond and Lovley, 2002;Küsel et al, 2008;Jerman et al, 2009), weakening these effects (dotted flat arrow in lower left, Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work at the Biocomplexity site showed that much of the basin is prone to anoxia, and that dissimilatory Fe(III) reduction is a particularly important anaerobic process that contributes significantly to the ecosystem C budget (Lipson et al, 2010). This process is generally thought to competitively inhibit methanogenesis by providing a more thermodynamically favorable respiratory pathway (Roden and Wetzel, 1996;Blodau, 2002;Bond and Lovley, 2002;Küsel et al, 2008;Jerman et al, 2009). And while CH 4 production has been studied in the Arctic Coastal Plain near Barrow, AK (Rhew et al, 2007;Zona et al, 2009;von Fischer et al, 2010), no studies have yet explored how Fe(III) reduction interacts with CH 4 production in this ecosystem.…”
Section: A Lipson Et Al: Arctic Coastal Tundra Ecosystemmentioning
confidence: 99%